2020
DOI: 10.1186/s12864-020-06894-3
|View full text |Cite
|
Sign up to set email alerts
|

PacBio single molecule long-read sequencing provides insight into the complexity and diversity of the Pinctada fucata martensii transcriptome

Abstract: Background The pearl oyster Pinctada fucata martensii is an economically valuable shellfish for seawater pearl production, and production of pearls depends on its growth. To date, the molecular mechanisms of the growth of this species remain poorly understood. The transcriptome sequencing has been considered to understanding of the complexity of mechanisms of the growth of P. f. martensii. The recently released genome sequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Chinese medicinal animal, obtaining a full-length transcriptome and understanding the structure of genes in G. gecko is a primary step in studying gene function, which is very important, yet it is still unknown. SMRT sequencing provides new knowledge of full-length sequences, which is confirmed to be useful for performing gene annotation and interpreting gene functions, especially for species lacking a reference genome [12,31]. In the present study, we obtained 882,273 CCSs, identified 746,317 FLNC, and then yielded 212,964 corrected isoforms with an average read length of 4,153 bp.…”
Section: Plos Onementioning
confidence: 74%
See 2 more Smart Citations
“…Chinese medicinal animal, obtaining a full-length transcriptome and understanding the structure of genes in G. gecko is a primary step in studying gene function, which is very important, yet it is still unknown. SMRT sequencing provides new knowledge of full-length sequences, which is confirmed to be useful for performing gene annotation and interpreting gene functions, especially for species lacking a reference genome [12,31]. In the present study, we obtained 882,273 CCSs, identified 746,317 FLNC, and then yielded 212,964 corrected isoforms with an average read length of 4,153 bp.…”
Section: Plos Onementioning
confidence: 74%
“…For decades, a substantial number of RNA-seq studies have been conducted to understand gene expression and molecular mechanisms, moreover, RNAseq is particularly widely used for nonmodel species that lack a reference genome [6][7][8][9], it provides insights into mRNA splicing and gene expression and has been used to screen candidate genes; however, the gene structure and full-length sequence are limited [10,11]. In addition, the extent of alternative splicing (AS) and transcriptome diversity remain largely unknown due to its short read length [12]. Recently, the single molecule real-time (SMRT) sequencing technique revolutionized the limitation of short read sequences and fragmentation, and postsequencing assembly are not needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through integrated transcriptome and metabolome analyses, Hao et al (2019) assessed the metabolic and transcript changes between the fast-growing and slowgrowing P. f. martensii groups and determined the mechanism underlying this phenomenon. Pacific Bioscience (PacBio) singlemolecular sequencing technologies, an emerging transcriptome sequencing method, enables researchers to understand the complexity and diversity of the molecular mechanisms of the growth of P. f. martensii (Zhang et al, 2020). Using a next-generation sequencing method and RNA-seq technology, Vaihiti et al performed gonad transcriptome analysis of the hermaphroditic P. margaritifera from several gonadic samples of males and females at different development stages.…”
Section: Growth Performance and Traitsmentioning
confidence: 99%
“…Stress-related molecules have been studied using Illumina sequencing. PacBio SMRT sequencing can provide information on transcript diversity, including alternative splicing (AS), alternative polyadenylation (APA), and long noncoding RNAs (lncRNAs) [ 7 ]. AS can generate various mRNAs and significantly enhance regulatory capacities and proteomic complexities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%